Rethinking machines. (Economist, 2001)
Part of a special section on technological innovations from the first quarter of 2001. Danny Hillis is a computing pioneer who has distinctive ideas on the relationship between technology and humanity. He first came to attention in the 1980s for his work on a computing technique called “massively parallel” processing. He then came up with the idea of a computer with 65,536 processors connected in a 12-dimensional “hypercube,” and he established a company called Thinking Machines to commercialize the concept. In 1985, the company made his idea a reality when it built its first product, the Connection Machine Model 1, which was explicitly modeled on the human brain. Hillis left the company in 1994 and began working on a clock that would run for 10,000 years. The first prototype of the clock was finished in 1999, and it is now housed in the Science Museum in London, England.